(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
The research studies the effect of the (Convolvulu arvens ) some biological aspects of Culex quingua fasciatus result shows a . The mortality insect in the first, second, third and fourth larval instars (75,55,50,465) trentant respectively in concentration 10% comparing with 5% in the control and the mortality of pupa for same extract and same concentration and(75,55,50,46,49% ) respectively was ( 46,42%)was comparing 1,2 % in the concentration. The statistical analysis show the moral average in results .the productions of adulte decreased from 127 eggs to 57,6 hot and cold concentration and 8,4 eggs female each female in concentrationof 10% moral result differences in result .